IL-6 and IL-10 gene polymorphisms in patients with aggressive periodontitis: effects on GCF, serum and clinic parameters - Emine PIRIM GORGUN; Hulya TOKER; Ertan Mahir KORKMAZ; Omer POYRAZ (Brazilian Oral Research)
Abstract Genetic variations observed in cytokines affect periodontitis susceptibility. The aim of this study was to investigate interleukin(IL)-6(-174) and IL-10(-597) gene polymorphisms in generalized aggressive periodontitis (GAgP) patients. Also, we aimed to evaluate the effects of IL-6 and IL-10 gene polymorphisms on the clinical outcomes of non-surgical periodontal therapy and cytokine levels in gingival crevicular fluid(GCF) and serum. Fifty-three patients with GAgP and 50 periodontally healthy individuals were included in this study. Clinical parameters, GCF and blood samples were collected at baseline and at 6-week. Non-surgical periodontal therapy was performed in patients with GAgP. Gene analysis were determined by PCR-RFLP(polymerase chain reaction-restriction fragment length polymorphism) and cytokine levels were determined by enzyme-linked immunosorbent assay(ELISA).GAgP patients showed significant improvement on clinical parameters after periodontal therapy(p<0.05). In the GAgP group, IL-6 GG genotype and G allele frequency were higher than in the control group. GCF IL-6 level was also significantly lower at 6-week in the GAgP group. Higher GCF IL-10 levelswere observed in patients carrying the IL-6 GG genotype than in those carrying the GC+CC genotype at baseline. In conclusion, IL-6(-174) and IL-10(-597) gene polymorphisms were found to be associated with GAgP and genotype distribution did not affect the outcome of non-surgical periodontal therapy, while patients with IL-6(-174) GG genotype had higher levels of GCF IL-10 levels.